Engaging With Biology by Asking Questions: Investigating Students' Interaction and Learning With an Artificial Intelligence-Enriched Textbook. (October 2020) - Koć-Januchta, Marta M.; Schönborn, Konrad J.; Tibell, Lena A. E.; Chaudhri, Vinay K.; Heller, H. Craig
Applying artificial intelligence (AI) to support science learning is a prominent aspect of the digital education revolution. This study investigates students' interaction and learning with an AI book, which enables the inputting of questions and receiving of suggested questions to understand biology, in comparison with a traditional E-book. Students ( n  = 16) in a tertiary biology course engaged with the topics of energy in cells and cell signaling. The AI book group ( n  = 6) interacted with the AI book first followed by the E-book, while the E-book group ( n  = 10) did so in reverse. Students responded to pre-/posttests and to cognitive load, motivation, and usability questionnaires; and three students were interviewed. All interactions with the books were automatically logged. Results revealed a learning gain and a similar pattern of feature use across both books. Nevertheless, asking questions with the AI book was associated with higher retention and correlated positively with viewing visual representations more often. Students with a higher intrinsic motivation to know and to experience stimulation perceived book usability more favorably. Interviews revealed that posing and receiving suggested questions was helpful, while ideas for future development included more personalized feedback. Future research shall explore how learning can be benefitted with the AI-enriched book.